Aerobic fitness, muscular strength and obesity in relation to risk of heart failure. Issue 22 (12th May 2017) - Crump, Casey; Sundquist, Jan; Winkleby, Marilyn A; Sundquist, Kristina
Abstract : Objective: Low physical fitness and obesity have been associated with higher risk of developing heart failure (HF), but their interactive effects are unknown. Elucidation of interactions among these common modifiable factors may help facilitate more effective primary prevention. Methods: We conducted a national cohort study to examine the interactive effects of aerobic fitness, muscular strength and body mass index (BMI) among 1 330 610 military conscripts in Sweden during 1969–1997 (97%–98% of all 18-year-old men) on risk of HF identified from inpatient and outpatient diagnoses through 2012 (maximum age 62 years). Results: There were 11 711 men diagnosed with HF in 37.8 million person-years of follow-up. Low aerobic fitness, low muscular strength and obesity were independently associated with higher risk of HF, after adjusting for each other, socioeconomic factors, other chronic diseases and family history of HF. The combination of low aerobic fitness and low muscular strength (lowest vs highest tertiles) was associated with a 1.7-fold risk of HF (95% CI 1.6 to 1.9; p<0.001; incidence rates per 100 000 person-years, 43.2 vs 10.8). These factors had positive additive and multiplicative interactions (p<0.001) and were associated with increased risk of HF even among men with normal BMI. Conclusions: Low aerobic fitness, low muscular strength and obesity at the age of 18 years were independently associated with higher risk of HF in adulthood, with interactive effects between aerobic fitness and muscular strength. These findings suggest that early-life interventions may help reduce the long-term risk of HF and should include both aerobic fitness and muscular strength, even among persons with normal BMI.